2008
DOI: 10.1016/j.jvs.2008.09.049
|View full text |Cite
|
Sign up to set email alerts
|

A current interpretation of popliteal vascular entrapment

Abstract: Functional popliteal artery entrapment is differentiated from anatomical entrapment by the absence of abnormal popliteal fossa anatomy. Although functional compression is a common entity in the general population, the precise etiology and natural history remains unknown. Magnetic resonance imaging clearly defines muscular variations within the popliteal fossa. In light of some of these variations, this article reviews embryological anatomy, diagnosis, classification, and treatment of the popliteal entrapment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 12 publications
0
59
0
1
Order By: Relevance
“…The symptoms of PAES occur due to arterial wall degeneration, which depends on the degree of compression, the magnitude of the forces exerted on the popliteal artery and the duration of compression. 13) Left untreated, the compression mechanism frequently results in the deterioration of the popliteal artery, which may progress to eventual occlusion. 14) Sinha, et al 15) reported that PAES occludes the popliteal artery in 24% of patients and changes the popliteal artery to poststenotic dilatation or aneurysmal formation in 13.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of PAES occur due to arterial wall degeneration, which depends on the degree of compression, the magnitude of the forces exerted on the popliteal artery and the duration of compression. 13) Left untreated, the compression mechanism frequently results in the deterioration of the popliteal artery, which may progress to eventual occlusion. 14) Sinha, et al 15) reported that PAES occludes the popliteal artery in 24% of patients and changes the popliteal artery to poststenotic dilatation or aneurysmal formation in 13.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Type III anomaly is characterized by an accessory slip of the medial head of the gastrocnemius forming a sling around the popliteal artery. The frequency of prevalence is as follows: type 1, 20%; type 2, 38%; and type 3, 26% [7]. In type IV anomaly, the normally positioned popliteal artery passes deep to the popliteus.…”
Section: Discussionmentioning
confidence: 99%
“…This "competition for space" between the primitive neurovascular bundle and various migrating muscles potentially predisposes to functional PAES. Contraction of the bulky, powerful MHGM within a confined space bordered by strong fascia and solid bone can result in forceful compression of the adjacent neurovascular bundle [1]. In these cases the anatomy in the popliteal fossa is 'normal' but variations in the position of the MHGM likely predispose to functional PAES.…”
Section: Embryological Developmentmentioning
confidence: 99%
“…Popliteal artery entrapment syndrome (PAES) is an important and often over looked differential diagnosis in the assessment of exertional leg pain. PAES is defined as a group of conditions in which compression of the popliteal artery, popliteal vein, and tibial nerve (singly or in combination) in the popliteal fossa by surrounding musculoskeletal structures occurs to a degree sufficient to cause vascular and neurogenic symptoms [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation